Identification of Vibrio cholerae O1 strains of the El Tor biovar sensitive to polymyxin B and their molecular genetic analysis - S. P. Zadnova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2021)
The aim of the work was the identification and genetic characterization of Vibrio cholerae O1 strains of the El Tor biovar sensitive to polymyxin B among isolates imported to Russia.Materials and methods. We used 56 toxigenic and non-toxigenic strains of V. cholerae isolated from patients and from the environmental samples on the territory of Russia in 1970-2020. Resistance to polymyxin B was determined according to MR4.2.2218-07. The ability of strains to form a biofilm on the abiotic surface was assessed by a photometric method. Nucleotide sequences of genes were determined using UGENE 1.32 and MEGA X software. Phylogenetic analysis and tree construction were performed using "maximum parsimony" method in MEGA X software.Results and discussion. Two genetically modified strains of V. cholerae O1 biovar El Tor, M1509 and 3265/80, which were imported to Russia from India in 2012 and 2014, respectively, were identified. The analysis of 12 genes responsible for the resistance of V. cholerae O1 biovar El Tor strains to polymyxin B demonstrated that these strains contain the allele of the carRS gene, which is typical for all strains of cholera vibrio sensitive to polymyxin B. Study of V. cholerae M1509 and 3265/80 phylogeny based on SNP analysis showed that they fall into the same cluster with isolates containing the carRS allele isolated in India (2015) and Bangladesh (2018). V. cholerae M1509 and 3256/8 strains had the ability to form a biofilm similar to those observed in other genetically modified strains of cholera vibrio included into analysis.Conclusion. Highly virulent strains of the cholera agent with altered diagnostically significant features are imported into Russia, which should be taken into account when identifying V. cholerae O1 biovar El Tor strains isolated from patients and environmental samples during monitoring studies.